2021
DOI: 10.3389/fimmu.2021.718563
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Cytotoxic T Cells Increase in Placenta after Intrauterine Inflammation

Abstract: CD8+ T cells recognize non-self antigen by MHC class I molecules and kill the target cells by the release of proinflammatory cytokines such as interferon gamma (IFN-γ) and tumor necrosis factor alpha (TNF-α). Our group previously reported an increase of CD8+ T‐cell trafficking in the placenta with exposure to Lipopolysaccharides (LPS). CD8+ cytotoxic T cells have been classified into distinct subsets based upon cytokine production: Tc1 cells produce IFN-γ, Tc2 cells produce interleukin 4 (IL-4). Accordingly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…At 3hpi and 6hpi, CD45 + leukocyte infiltrates in the placenta were significantly increased in LPS + PBS group compared to PBS + PBS group, while maternal treatment of DNAC significantly decreased CD45 + leukocytes infiltration in LPS + DNAC group compared to LPS + PBS group (Figure 2B, p < 0.05). Similarly, as our prior study demonstrated, CD45 + leukocyte infiltration in placenta increased with LPS-exposure at 6hpi of E17 (Lei et al, 2017;Liu et al, 2021). At 12hpi, CD45 + leukocytes infiltration in the placenta did not show any significant difference between groups (Figure 2B).…”
Section: Maternal Administration Of Dnac Alteredsupporting
confidence: 83%
See 2 more Smart Citations
“…At 3hpi and 6hpi, CD45 + leukocyte infiltrates in the placenta were significantly increased in LPS + PBS group compared to PBS + PBS group, while maternal treatment of DNAC significantly decreased CD45 + leukocytes infiltration in LPS + DNAC group compared to LPS + PBS group (Figure 2B, p < 0.05). Similarly, as our prior study demonstrated, CD45 + leukocyte infiltration in placenta increased with LPS-exposure at 6hpi of E17 (Lei et al, 2017;Liu et al, 2021). At 12hpi, CD45 + leukocytes infiltration in the placenta did not show any significant difference between groups (Figure 2B).…”
Section: Maternal Administration Of Dnac Alteredsupporting
confidence: 83%
“…The maternal-fetal interface supports multiple cellular immune systems comprising adaptive immune T cells and homeostatic innate immune cells such as macrophages. T cells have been shown to participate in placental pathological inflammation during pregnancy (Lee et al, 2011;Arenas-Hernandez et al, 2019;Liu et al, 2021). We proved that DNAC prevents CD3 + /CD45 + cells increased by LPS-induced placental inflammations, but free NAC treatment does not.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A significantly increased number of Type 1 CD8+ T cells and the ratio of Type 1 CD8+ T cells to Type 2 CD8+ T cells were detected (89). Simultaneously, more pro-inflammatory cytokines and further destructions in the tissue that indicated enhanced immune and inflammatory responses may induce lasting chronic inflammation (89). Of note, Chen et al found the incidence rate of periodontitis in the subjects with gout was significantly higher than that in the comparison cohort, while the risk of periodontitis in gout patients using colchicine was significantly lower (90).…”
Section: The Immune Enhancement Effect Of Ua or Msu For Periodontitismentioning
confidence: 97%
“…Liu et al. demonstrated that the Type 1 CD8+ T cells were the main participants in the inflammatory cytotoxic responses when exposed to LPS ( 89 ). A significantly increased number of Type 1 CD8+ T cells and the ratio of Type 1 CD8+ T cells to Type 2 CD8+ T cells were detected ( 89 ).…”
Section: The Possible Interactive Relationship Between Hyperuricemia ...mentioning
confidence: 99%